Anthropometric, morphological and somatotype characteristics of athletes of the Brazilian Men's volleyball team: an 11-year descriptive study - Edio Luiz Petroski; Jefferson Del Fraro; Yara Lucy Fidelix; Diego Augusto Santos Silva; Cândido Simões Pires-Neto; Antônio Carlos Dourado; Marcos Augusto Rocha; Luiz Cláudio Reeberg Stanganelli; Percy Oncken; Filomena S. Vieira (Universidade Federal de Santa Catarina, 2013)
This study analyzed the anthropometric and morphological characteristics ofthe adult male players in the Brazilian volleyball team for 11 years. The sample comprised 92 athletes selected for the national team from 1995 to 2005. Anthropometric measures were collected and body composition and somatotype components were estimated. Oneway ANOVA and the Bonferroni test were used for descriptive statistical analysis, and the level of significance was set at p<0.05. Along the 11 years, there was a significant increase in the flexed arm perimeter, humerus diameter and lean mass. Skinfold thickness and percent body fat tended to decrease. Height increased and was greater than 1.97 m. The somatotype of the volleyball players in the Brazilian team changed along the years. Ectomorphic and mesomorphic somatotypes were the most frequent. In 11 years, the athletes selected for the Brazilian team had an increase in body mass and a decrease in skinfold thickness and percent body fat. The most frequent anthropometric classifications were mesomorph-ectomorph for five years, followed by mesomorphic-ectomorph for three years, which suggests that greater height and low body fat were taken into consideration when selecting athletes for the national team